Impact of tumor necrosis factor receptor p55 deficiency in susceptibility of C57BL/6 mice to infection with Leishmania (Leishmania) amazonensis - Cargnelutti, Diego Esteban (2014)
Tumor necrosis factor (TNF) is involved in host resistance to several intracellular pathogens. Although the critical role of TNF receptor (TNFR)p55 in Leishmania (Leishmania) major infection has been demonstrated, the impact of TNFRp55 deficiency on L. (L.) amazonensis infection has not been explored. L. (L.) amazonensis-infected TNFRp55−/− mice failed to resolve lesions, whereas C57BL/6 wild-type mice completely healed. The susceptibility of the TNFRp55−/− mice was characterized by higher lesion size and histopathological damage in comparison with the wild-type mice. A marked increased of the splenic index was observed in the TNFRp55−/− mice after 15 weeks infection. These results show that in the absence of TNFRp55, L. (L.) amazonensis-infected knockout mice fail to resolve lesions, whereas wild-type mice completely heal.